THE EFFECTS OF SO2 AND NH3 ON THE ATMOSPHERIC CORROSION OF GALVANIZED IRON SHEET - DEHRI, I; YAZICI, B; ERBIL, M; GALIP, H (Pergamon-Elsevier Science Ltd, 1994)
The corrosive effects of SO2 and NH3 gases on zinc and galvanized iron sheet have been investigated. For this purpose, analytical and electrochemical methods were used in laboratory conditions with varying relative humidity values (70-100%). Electrochemically, the anodic current-potential curves of zinc have been obtained in solutions of different concentrations of sulphuric acid (0.50, 0.25, 0.10 M) and ammonia (pH = 13.20). The results indicate that, the corrosion rate of zinc and galvanized iron increases as the relative humidity increases in SO2 containing medium but the corrosion rate is not related much to relative humidity in NH3 containing environment. At the same time, it has been observed that zinc does not get passive in H2SO4 containing medium but it does become passive in ammonia solution. This passivation of zinc in NH3 is due to the formation of a complex [Zn(NH3)(4)(OH)(2)] on the metal surface by OH- and NH3.
Keywords: Zinc; Film